A NEW SAN LUIS POTOSIECIES OF TRIATOMA IN MEXICO - MAZZOTTI, LUIS (Universidad Nacional Autónoma de México, CD MEXICO, DF, MEX, 1940)
Eoxenos is a synonym of Iberoxenos These are primitive Estrepsiptera in which the free adult [female][female] are almost normally formed although wingless and possess antennae, mouth, compound eyes and feet; the [male][male] have 5-jointed tarsi ending i
CIENC MEX
Keywords: NEW SPECIES, TRIATOMA, MEXICO; MULTIDISCIPLINARIA; ETOLOGIA; INSECTOS